Sistem Pendukung Keputusan Penilaian Kinerja Mahasiswa KIP Kuliah dengan Penerapan Metode TOPSIS dan PROMETHEE - Noni Apriliani Yulia Putri; Ridho Taufiq Subagio; Marsani Asfi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
CIC University is one of the Private Universities (PTS) in the Computer Sector which is located in the city of Cirebon. CIC University's consistency in the field of IT (Information Technology) so that college students in it can apply IT knowledge to campus facilities. One of the systems currently not owned by CIC University is a decision support system for assessing the performance of college students receiving KIP Kuliah. Assessment of college student performance, especially for scholarship recipients at a university, is a very important form of activity to evaluate performance in improving the quality of performance of scholarship recipients, as a form of measurable responsibility as scholarship recipients both academically and non-academicly and as a form of assessing whether students is still eligible to be awarded a scholarship in the next semester or year. This study discusses the performance assessment of KIP Lecturer recipients using UML (Unified Modeling Language) as a tool in analysis and design, the PHP Hypertext Preprocessor programming language with the CodeIgniter framework, and MySQL as data storage media. Performance appraisal is calculated by a combination of the TOPSIS method and the PROMETHEE method. TOPSIS method is used to calculate the weight of each criterion, while the PROMETHEE method is used to analyze alternative ranking calculations. Testing this application is done by the Black Box method. The result of this research is the Application of Performance Assessment of College Students receiving KIP Kuliah at Catur Insan Cendekia University which aims to assist the Student Affairs Bureau in assessing the performance of college students receiving KIP Kuliah quickly